AUDIT SISTEM INFORMASI MENGGUNAKAN FRAMEWORK COBIT 5 PADA SIAKAD INSTITUT TEKNOLOGI DAN BISNIS (ITB) SEMARANG - Anggun Putri Dwi Meilina; Aji Priyambodo; Andreas Tigor Oktaga (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) - Institut Teknologi dan Bisnis Semarang, 2024)
This research aims to carry out an information system audit on the Academic Information System (SIAKAD) at the Institute of Technology and Business (ITB) Semarang by utilizing the COBIT 5 Framework. An information system audit is a crucial step to assess the effectiveness, effciency and security of the informatiion system operated by organization. COBIT 5 as an internationally recognized Framework, provides a structured approach to ensuring the governance and management of information technology effective.his research uses an evaluation methodology for key processes in COBIT 5, such as risk management, IT service management, and IT resource management, which are relevant to the implementation of SIAKAD. Data was obtained through interviews, observation and review of internal documents. The audit results comply with several COBIT 5 standards, although there are several areas that still require improvement to increase system perfomance and security. It is hoped that this researcher can provide strategic recommendations for ITB Semarang to optimize academic information systems, as well as become a reference for other institutions that wish to implement COBIT 5 in information system audits.